2021
DOI: 10.35848/1882-0786/abec58
|View full text |Cite
|
Sign up to set email alerts
|

Realizing forming-free characteristic by doping Ag into HfO2-based RRAM

Abstract: In this work, Ag-doped HfO2-based resistive random access memory (RRAM) with high on-off ratio, low-power consumption and forming-free properties was investigated. We propose the fabrication flow of the RRAM with via-hole structure. After doping Ag into HfO2 as the switching layer, the devices could execute resistive switching without a high-voltage forming process. The conduction mechanism was subsequently validated by a current fitting analysis. Electric field simulation was also utilized to observe the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Sokolov et al adjusted oxygen vacancy distribution in HfO 2 films by introducing the defects so that the oxidation pulse time is reduced. Moreover, the RRAM device with the Ag TE is mainly due to the strong electrochemical activity of Ag, which is easy to form metallic Ag CFs in the dielectric layer. , Therefore, for the prepared HfO 2 -based RRAM device, because of using Ag as the TE, it is possible that Ag CFs and oxygen vacancy CFs jointly play a role in the RS of the device. Then, we conducted a series of microscopic characterization experiments on various device films before and after electrical testing to confirm this theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sokolov et al adjusted oxygen vacancy distribution in HfO 2 films by introducing the defects so that the oxidation pulse time is reduced. Moreover, the RRAM device with the Ag TE is mainly due to the strong electrochemical activity of Ag, which is easy to form metallic Ag CFs in the dielectric layer. , Therefore, for the prepared HfO 2 -based RRAM device, because of using Ag as the TE, it is possible that Ag CFs and oxygen vacancy CFs jointly play a role in the RS of the device. Then, we conducted a series of microscopic characterization experiments on various device films before and after electrical testing to confirm this theory.…”
Section: Resultsmentioning
confidence: 99%
“…Paul et al 45 reported that doping Al nanoparticles in HfO 2 helps improve the RS ratio, retention, and stability by adjusting the oxygen vacancies, but may slow down the speed of devices, which are best suitable for applications in neuromorphic synapses and multilevel devices. Interestingly, Wu et al 46 achieved forming-free characteristics and low switching currents by body doping Ag into HfO 2 . The body doping and uniformly distributed Ag nanoparticles in the resistive layer HfO 2 form tapered Ag CFs under the electric field, with an electric field enhancement effect at the tapered tips.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, conductive filament formation is dominated by oxygen vacancies, and an appropriate amount of Ag can be used as conductive filaments to form contacts. [57][58][59] Consequently, RRAM devices can operate effectively under low-bias conditions. Ag concentration directly affects the electrical characteristics of RRAM devices.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we propose a novel nitrogen-oxyanion-doping (N-doping) method to improve the forming performance of HfO2 RRAM. Different from previous doping methods, which use metallic element (Al [9], Mg [10], Ge [11], Ag [12]) dopants in the form of cations or non-metallic element (N [13], [14], F [15]) dopants in the form of anions, we use nitrogen oxyanions to dope HfO2 RRAM. Magnetron sputtering is used to induce N-doping, where the high-energy plasma atmosphere promotes the chemical reactions between N, O and Hf.…”
Section: Introductionmentioning
confidence: 99%